2009
DOI: 10.1007/s00216-009-2601-7
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence properties of selected benzo[c]phenantridine alkaloids and studies of their interaction with CT DNA

Abstract: The spectral, especially fluorescence properties, of seven selected quaternary benzo[c]phenantridine alkaloids (sanguinarine, chelerythrine, chelirubine, sanguirubine, chelilutine, sanguilutine, and macarpine) were studied in presence and in absence of double-stranded DNA. This study has proved dramatic differences in fluorescence emission of all studied alkaloids in presence of calf thymus DNA in comparison to fluorescence of free alkaloids. The most remarkable are changes in emission spectra of macarpine, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 19 publications
1
33
1
1
Order By: Relevance
“…QBAs, a group of low molecular compounds with N-heteroatom, belong to the highly bioactive substances [1]. Some side effects were reported (toxic effect on some cellular level [2][3][4][5]) in addition to the beneficial pharmacological actions (antimicrobial, antiapoptotic, antiinflamatory etc. effects [6,7]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…QBAs, a group of low molecular compounds with N-heteroatom, belong to the highly bioactive substances [1]. Some side effects were reported (toxic effect on some cellular level [2][3][4][5]) in addition to the beneficial pharmacological actions (antimicrobial, antiapoptotic, antiinflamatory etc. effects [6,7]).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] The exact knowledge of physico-chemical characteristics is very important for correct interpretation of experiments concerning studies of interactions and behavior of the alkaloids at nearly physiological conditions. It is evident that the study of interactions [3][4][5][6] with biologically important macromolecules (i.e., receptors, transport proteins, nucleic acids etc. ), as Amresco ® , Solon, Ohio, USA) and sodium hydroxide (reagent grade purity, Penta, Chrudim, Czech Republic) solutions were used for the pH adjustment in a pH interval pH = 2 -11 with steps ∆pH = 0.2 -0.5.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, whereas sanguilutine and chelilutine exhibit antiproliferative and anti-microtubular activities (Slaninova et al 2001), sanguirubine, chelirubine, and macarpine are antiproliferative and pro-apoptotic, as has been well documented (Slaninova et al 2007). Macarpine and sanguirubine show a considerable fluorescence shift when bound to deoxyribonucleic acid (DNA), a property which makes them useful as fluorescent probes (Urbanova et al 2009). Macarpine seems to be a promising novel cell-permeant DNA dye for livecell imaging and flow cytometry sorting (Slaninova et al 2016).…”
mentioning
confidence: 99%
“…Prado et al (2004) reported that nitidine and fagaronine bind to duplex DNA by the mechanism of intercalation. Recently a comparative study on the binding of sanguinarine, nitidine, and chelerythrine with calf thymus DNA, poly(dG-dC).poly(dG-dC), poly (dA-dT).poly(dA-dT), and several sequence-designed double-stranded oligonucleotides was performed using spectrophotometric and spectrofluorimetric techniques to elucidate their sequence selectivity for DNA binding (Bai et al 2006;Urbanova et al 2009). Fluorescence titration of DNA with three alkaloids was performed in acidic buffer at pH 5.30 to ensure that these alkaloids exist exclusively as the iminium form (Bai et al 2006).…”
Section: Sanguinarine (Iminium)-triplex Dna Interactionmentioning
confidence: 99%